Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve the system of equations:
[tex]\[ \begin{align*} 1) &\quad 5 - 3y = 18, \\ 2) &\quad 3s^2 - y = 12, \end{align*} \][/tex]
we will first find the value of [tex]\(y\)[/tex] from the first equation, and then use it to find [tex]\(s\)[/tex] from the second equation. Let's proceed step-by-step.
### Step 1: Solve for [tex]\(y\)[/tex] from the first equation
The first equation is:
[tex]\[ 5 - 3y = 18 \][/tex]
Subtract 5 from both sides to isolate the term involving [tex]\(y\)[/tex]:
[tex]\[ -3y = 18 - 5 \][/tex]
Simplify the right-hand side:
[tex]\[ -3y = 13 \][/tex]
Divide both sides by -3 to solve for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{13}{-3} \][/tex]
So,
[tex]\[ y = -4.\overline{3} \][/tex]
### Step 2: Substitute [tex]\(y\)[/tex] into the second equation to solve for [tex]\(s\)[/tex]
The second equation is:
[tex]\[ 3s^2 - y = 12 \][/tex]
Substitute [tex]\(y = -4.\overline{3}\)[/tex] into the equation:
[tex]\[ 3s^2 - \left(-4.\overline{3}\right) = 12 \][/tex]
Simplify the left-hand side:
[tex]\[ 3s^2 + 4.\overline{3} = 12 \][/tex]
Next, we need to isolate [tex]\(s^2\)[/tex]. Subtract [tex]\(4.\overline{3}\)[/tex] from both sides:
[tex]\[ 3s^2 = 12 - 4.\overline{3} \][/tex]
We know that [tex]\(4.\overline{3}\)[/tex] is equivalent to [tex]\(\frac{13}{3}\)[/tex], so the equation becomes:
[tex]\[ 3s^2 = 12 - \frac{13}{3} \][/tex]
Convert 12 into a fraction with the same denominator:
[tex]\[ 12 = \frac{36}{3} \][/tex]
Now, subtract the fractions:
[tex]\[ 3s^2 = \frac{36}{3} - \frac{13}{3} \][/tex]
Combine the fractions:
[tex]\[ 3s^2 = \frac{36 - 13}{3} \][/tex]
Simplify the numerator:
[tex]\[ 3s^2 = \frac{23}{3} \][/tex]
Divide both sides by 3 to solve for [tex]\(s^2\)[/tex]:
[tex]\[ s^2 = \frac{23}{9} \][/tex]
### Step 3: Solve for [tex]\(s\)[/tex]
To find [tex]\(s\)[/tex], take the square root of both sides:
[tex]\[ s = \sqrt{\frac{23}{9}} \][/tex]
Simplify by finding the square root of the numerator and the denominator separately:
[tex]\[ s = \frac{\sqrt{23}}{\sqrt{9}} = \frac{\sqrt{23}}{3} \][/tex]
Thus, the numerical value of [tex]\(s\)[/tex] is approximately:
[tex]\[ s \approx 1.5986 \][/tex]
### Summary of Solutions
Therefore, the solutions are:
[tex]\[ y \approx -4.3333, \quad s^2 \approx 2.5556, \quad s \approx 1.5986 \][/tex]
These steps provide a clear and detailed solution to the given system of equations.
[tex]\[ \begin{align*} 1) &\quad 5 - 3y = 18, \\ 2) &\quad 3s^2 - y = 12, \end{align*} \][/tex]
we will first find the value of [tex]\(y\)[/tex] from the first equation, and then use it to find [tex]\(s\)[/tex] from the second equation. Let's proceed step-by-step.
### Step 1: Solve for [tex]\(y\)[/tex] from the first equation
The first equation is:
[tex]\[ 5 - 3y = 18 \][/tex]
Subtract 5 from both sides to isolate the term involving [tex]\(y\)[/tex]:
[tex]\[ -3y = 18 - 5 \][/tex]
Simplify the right-hand side:
[tex]\[ -3y = 13 \][/tex]
Divide both sides by -3 to solve for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{13}{-3} \][/tex]
So,
[tex]\[ y = -4.\overline{3} \][/tex]
### Step 2: Substitute [tex]\(y\)[/tex] into the second equation to solve for [tex]\(s\)[/tex]
The second equation is:
[tex]\[ 3s^2 - y = 12 \][/tex]
Substitute [tex]\(y = -4.\overline{3}\)[/tex] into the equation:
[tex]\[ 3s^2 - \left(-4.\overline{3}\right) = 12 \][/tex]
Simplify the left-hand side:
[tex]\[ 3s^2 + 4.\overline{3} = 12 \][/tex]
Next, we need to isolate [tex]\(s^2\)[/tex]. Subtract [tex]\(4.\overline{3}\)[/tex] from both sides:
[tex]\[ 3s^2 = 12 - 4.\overline{3} \][/tex]
We know that [tex]\(4.\overline{3}\)[/tex] is equivalent to [tex]\(\frac{13}{3}\)[/tex], so the equation becomes:
[tex]\[ 3s^2 = 12 - \frac{13}{3} \][/tex]
Convert 12 into a fraction with the same denominator:
[tex]\[ 12 = \frac{36}{3} \][/tex]
Now, subtract the fractions:
[tex]\[ 3s^2 = \frac{36}{3} - \frac{13}{3} \][/tex]
Combine the fractions:
[tex]\[ 3s^2 = \frac{36 - 13}{3} \][/tex]
Simplify the numerator:
[tex]\[ 3s^2 = \frac{23}{3} \][/tex]
Divide both sides by 3 to solve for [tex]\(s^2\)[/tex]:
[tex]\[ s^2 = \frac{23}{9} \][/tex]
### Step 3: Solve for [tex]\(s\)[/tex]
To find [tex]\(s\)[/tex], take the square root of both sides:
[tex]\[ s = \sqrt{\frac{23}{9}} \][/tex]
Simplify by finding the square root of the numerator and the denominator separately:
[tex]\[ s = \frac{\sqrt{23}}{\sqrt{9}} = \frac{\sqrt{23}}{3} \][/tex]
Thus, the numerical value of [tex]\(s\)[/tex] is approximately:
[tex]\[ s \approx 1.5986 \][/tex]
### Summary of Solutions
Therefore, the solutions are:
[tex]\[ y \approx -4.3333, \quad s^2 \approx 2.5556, \quad s \approx 1.5986 \][/tex]
These steps provide a clear and detailed solution to the given system of equations.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.